Nariginase of Aspergillus niger: Production optimization by response surface methodology and utilisation of ultrasound for extraction - Rosa, Cristiani Barros da Silva; Borsato, Dionísio; Buzato, João Batista; Celligoi, Maria Antonia Pedrine Colabone (Semina: Ciências Agrárias, 2011)
Brazil is the world's largest producer of orange and concentrated juice for export. Concentrated juice with high levels of naringin has excessive bitterness, which reduces the quality and value on the market. The debittering can be obtained by using naringinase, an enzymatic complex that degrades naringin. This study reports the production of naringinase by Aspergillus niger 426 utilizing both sugar cane molasses as carbon source and yeast extract as nitrogen source. Naringin was used as inducer. Five nitrogen sources were studied and yeast extract was found as the best one as 225.6 mU/mL of naringinase activity at 120 hours of fermentation was achivied. For optimization of naringinase production it was applied response-surface methodology, with 22 incomplete factorial design. An activity value of 354.26 mU/mL of naringinase was achivied when as independent variables yeast extract (14.0g/L) and naringin (0.2g/L) were used. When applied ultrasound waves at 20 kHz of intensity for 2 minutes in the fermented broth, the activity reached the highest value of 473.6 mU/mL. Thus, naringinase, this enzyme of great potential for biotechnological applications, has its production increased by using statistical design and ultrasound.